LEGALITY ASPECTS ON EXPORT READINESS OF MSME PRODUCTS FROM UPSTREAM TO DOWNSTREAM - Purwaningsih, Endang; Muslikh, Muslikh; Suhaeri, Suhaeri; Santoso, Jarot Tri Bowo; Basrowi, Basrowi (Jurnal Ilmiah Galuh Justisi, 2024)
PTUPT's research partners for the 3rd year are the Yogyakarta Traditional Food and Beverage Association (ASMAMITRA), and Central Java's Anugrah Sukses Mandiri (ASM). The issues discussed are partners' efforts to prepare complete export documents in an effort to protect and commercialize their products and readiness from upstream to downstream MSME actors in export efforts. This research is applied research, using a participatory research approach and a sociological approach, focusing on applying the model made in the previous year (2022) and analyzing the legality aspect of readiness. Based on the results of the research, partners' efforts to prepare complete export documents in an effort to protect and commercialize their products have been carried out by partners, namely MSME actors by cooperating with the role of stakeholders, in this case researchers, concerned foundations , banking, and MSME associations supported by empowerment by related agencies and local governments. , likewise with regard to readiness from upstream to downstream MSME players in export efforts have not been maximally carried out, especially the readiness of legal aspects has not been completely fulfilled, and requires a helping hand as well as assistance and facilitation of various parties.